2009
DOI: 10.2202/1475-3693.1156
|View full text |Cite
|
Sign up to set email alerts
|

International Portfolio Inflows to GCC Markets: Are There Any General Patterns?

Abstract: In this paper, we document the main factors underlying the foreign portfolio inflows to Gulf Corporation Council countries (hereafter GCC) by employing a recently published database of cross-country portfolio holdings by the International Monetary Fund. We find that bilateral factors such as trade volume and debt to GDP ratio between the source and GCC (host) countries play a truly significant role in determining the volume of cross border portfolio inflows to GCC markets. Particularly, there is a strong corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
10
1
Order By: Relevance
“…In addition, despite the difference in the country sample, the empirical results in column 2 and 4 are also in line with the works of Lane and Milesi-Ferretti (2005) and Balli et al (2009), reinforcing this study's finding that bilateral trade has, indeed, played an important role in encouraging cross-border portfolio investments in the APT markets.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, despite the difference in the country sample, the empirical results in column 2 and 4 are also in line with the works of Lane and Milesi-Ferretti (2005) and Balli et al (2009), reinforcing this study's finding that bilateral trade has, indeed, played an important role in encouraging cross-border portfolio investments in the APT markets.…”
Section: Resultssupporting
confidence: 86%
“…This appears to suggest that during the 2000s the relaxation of the financial market restrictions in the region has actually played an insignificant role in encouraging foreign portfolio investments. In addition, the finding also contradicts the evidence of Balli et al (2009), who found that the relaxation of capital controls in host country (proxied by the Chinn-Ito index) indeed enhanced foreign portfolio holdings in the GCC markets.…”
contrasting
confidence: 91%
“…Some recent papers that have estimated empirical gravity equations for equity, bond and bank holdings include Ahearne et al (2004), Aviat and Coeurdacier (2007), Balli (2008), Balli et al (2008), Balta and Delgado (2008), Berkel (2007), Bertaut and Kole (2004), Buch (2000Buch ( , 2002, Chan et al (2005) Gelos and Wei (2005), Ghosh and Wolf (2000), Hahm and Shin (2009), Jeanneau and Micu (2002), Kim et al (2007), Kim et al (2006), Lane and Milesi-Ferretti (2005a,b), Lane (2005), Lee (2008), Martin and Rey (2004), Pendle (2007), Portes and Rey (2005), Portes et al (2001), Rose and Spiegel (2004), Veronique and Benassy-Quere (2006), Vlachos (2004) and Yu (2009).…”
mentioning
confidence: 99%
“…documented by Balli et al (2009). Increased financial and economic integration as well as the changes in the geo-political and geo-economic environments in the aftermath of the 9/11 attacks are the likely reasons for the higher intra-regional private capital flows among the GCC countries.…”
Section: Introductionmentioning
confidence: 99%